The Effectiveness Of Website/Webblog-Based Mosque Management Information Systems In Providing Accountable Information In Pekalongan City - Agus Arwani; Muhamad Masrur; Nasrul Khakim (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
The mosque organization is a public sector organization, which manages the resources and activities in the mosque. The management and resources in the mosque are mostly done voluntarily. The development of information technology (IT) has provided various means for management in managing business and decision making. However, the measurement or assessment of the quality of an effective information system is difficult to do directly such as cost-benefit measurement. Research method in this research use field research with descriptive and quantitative approach. The results of this study descriptively obtained that the outline that the quality system, quality information, process quality, collaborative quality and service quality Mosque-based Mosque website run effectively and obtained accountable information in the city of Pekalongan. That the management of mosque based Mosque Website in Pekalongan city has been run effectively because it has been using the governance of mosque information system by using DeLone and McLean Model of Information System Success which includes system quality management, Collaborative quality and service quality of Mosque-based Mosque website in Pekalongan City